2005
DOI: 10.1002/sia.1942
|View full text |Cite
|
Sign up to set email alerts
|

Self‐recovery function of p(1×1)‐Sc‐O/W(100) system used as Schottky emitter

Abstract: The effects of heating temperature for the preparation of an Sc-O/W(100) surface were investigated. Surface properties of the Sc-O/W(100) surface prepared by heating at ∼1600 and ∼1700 K were significantly different from those prepared at ∼1500 K, which is the operating temperature of the Sc-O/W(100) emitter. By heating at ∼1700 K the p(1×1) structure formed by Sc-O complexes was confirmed, whereas the p(2×1)-p(1×2) double-domain structure was obtained by heating at ∼1500 K. The surface properties prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previous studies [4][5][6][7][8][9][10][11][12][13] have revealed that the Sc-O/W(1 0 0) surface has two phases with surface atomic arrangements of the (1 Â 1) and (2 Â 1)-(1 Â 2) structures at high temperature. The (2 Â 1)-(1 Â 2)-Sc-O/W(1 0 0) surface is formed by heating at 1500 K in oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [4][5][6][7][8][9][10][11][12][13] have revealed that the Sc-O/W(1 0 0) surface has two phases with surface atomic arrangements of the (1 Â 1) and (2 Â 1)-(1 Â 2) structures at high temperature. The (2 Â 1)-(1 Â 2)-Sc-O/W(1 0 0) surface is formed by heating at 1500 K in oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the authors have been involved in the surface characterization of the Sc-O/W(1 0 0) system using Auger electron spectroscopy (AES), low-energy electron diffraction (LEED), and work function measurement at high temperature [4][5][6][7][8][9][10][11][12][13]. Previous studies [4][5][6][7][8][9][10][11][12][13] have revealed that the Sc-O/W(1 0 0) surface has two phases with surface atomic arrangements of the (1 Â 1) and (2 Â 1)-(1 Â 2) structures at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The zirconium and oxygen adsorbed onto the cathode surface also reduced the work function; thus, the cathode emission current was greatly increased. Lida, S and Nagatomi, T studied a type of Sc-O/W(100) emitter used as Schottky emitter [38]. Their research indicated that Sc-O complexes have a lower work function and self-recovery function against residual gas.…”
Section: Analysis Of High Emission Characteristics Of Scandate Cathodmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] Previous studies have revealed that the Sc-O / W͑100͒ system has two phases at high temperature. The surface providing the excellent electron emission properties is considered to be formed only under limited preparation and operating conditions of the Sc-O / W͑100͒ emitter.…”
Section: Introductionmentioning
confidence: 99%